Defining a probabilistic translation dictionaries algebra - Simões, Alberto (2013)
Probabilistic Translation Dictionaries are around for some time, but there is a lack of a formal definition for their structure and base operations. In this article we start by discussing what these resources are, what researchers are using them for, and what tools can be used to create this them. Including a formal definition and a proposal for a XML schema for dictionaries interchange. Follows a discussion of a set of useful operations that can be performed over probabilistic translation dictionaries, like union, intersection, domain restriction and compo- sition. Together with this algebra formalization some insights on the operations usefulness and application are presented.